The International Olympic Committee Consensus Statement on age determination in high-level young athletes - Engebretsen, L.; Steffen, K.; Bahr, R.; Broderick, C.; Dvorak, J.; Janarv, P. M.; Johnson, A.; Leglise, M.; Mamisch, T. C.; McKay, D.; Micheli, L.; Schamasch, P.; et al. (British Journal of Sports Medicine, 2010)
Most youth sports around the world are classified on the basis of chronological age to guarantee equal chances within each of the different age groups. At the elite level, international sporting federations organise competitions in various age classes ranging from as low as under-13 up to under-21, depending on the sport. In August 2010, the International Olympic Committee (IOC) is conducting the first Youth Olympic Games in Singapore for 14-18-year-old athletes.